Industrial policy for a sustainable growth path - Karl Aiginger (WWWforEurope, 2014)
Industrial policy is back on the agenda and the consensus is that it must be different "this time" from the past. We redefine industrial policy for industrialised countries as a strategy to promote "high-road competitiveness", understood as the ability of an economy to achieve "Beyond-GDP" Goals. "High-road strategies" are based on advanced skills, innovation, supporting institutions, ecological ambition and an activating social policy. This "new industrial policy" is systemic, working in alignment with other policy strands and supporting social and environmental goals; it affects the structure of the economy as the whole not only the manufacturing sector. Short-term actions, such as protecting employment in unviable companies, low prices for fossil fuels, or reducing wages in high-income economies are counterproductive. To pursue an industrial policy that targets society's ultimate goals without public micromanagement will be challenging. It could be achieved (i) by setting incentives, particularly those impacting on technical progress (e.g. to make it less labour-saving and more energy-saving), (ii) by the use of the important role governments have in the education and research sectors, (iii) by greater public awareness and (iv) if consumer preferences will call for socio-ecological transition.
Keywords: H50; L16; L50; O20; O32; O38; O40; Q30; Q40; Q50; 330; New industrial policy; climate change; competitiveness; innovation strategy